Altered Calcium Metabolism in Epileptic Children on Anticonvulsants. Issue 5781 (23rd October 1971) - Hunter, John; Maxwell, J. D.; Stewart, D. A.; Parsons, Valerie; Williams, Roger
Abstract : A survey of 105 epileptic children aged 10-16 years at a residential school who were taking anticonvulsant drugs showed reduced serum calcium levels in 30% and a raised serum alkaline phosphatase in 24%. Urinary D-glucaric acid excretion, a quantitative index of hepatic enzyme induction, was raised in 94% of the children, and statistical analysis showed a significant inverse correlation with the level of serum calcium. These findings give further support for the view that an important factor in the development of the hypocalcaemia and occasional clinical osteomalacia in epileptics on anticonvulsant drugs is an alteration of vitamin-D metabolism in the liver as a result of microsomal enzyme induction. As a consequence there is an increased requirement for vitamin D which may not be met by average intakes in Britain.